Assessment the impact of the torus tubarius correction by power-assisted technique on the equipressor eustachian tube function - K.V. Liakh; A.L. Kosakovskyi; Ya.V. Shkorbotun (Group of Companies Med Expert, LLC, 2023)
Purpose of the research is to evaluate the impact of the torus tubarius correction by microdebrider technique on the eustachian tube function in children without middle ear pathology. Materials and methods. 115 children aged 3 to 12 years participated in the study. All children underwent endoscopic modified microdebridement adenotomy for the first time, which, in the case of tubal hypertrophy (we analyzed the frequency of this phenomenon), was combined with its correction by the microdebridement method. For the next stage of the research, we selected 19 children, who had preoperative intratympanic pressure monitoring results more than -100 daPa and who hadn't concomitant tonsil hypertrophy (19 children). Control measurement was done on days 1 and 8-10 after the intervention. Depending on the presence/absence of concomitant hypertrophy of the torus tubarius, patients were divided into the main (11 patients) and control (8 patients) groups. The analysis was carried out using the STATISTICA program. Results. 36 patients were diagnosed with torus tubarius hypertrophy. When comparing intratympanic pressure on the 1st day after the intervention in patients of the main and control groups, a significant difference in values was found (-144.37±41.09/-95.00±27.90 daPa). On day 8-10, the intratympanic pressure data in patients of both groups did not differ from each other (-39.15±14.85 daPa in the main and -33.87±19.57 daPa in the control groups) and preoperative values in both groups. Conclusions. Hypertrophy of the torus tubarius is noted in 31.3% of patients with primary adenotomy. The microdebrider technique method of torus tubarius correction is safe in view of the equipressor function of the auditory tube. The research was carried out in accordance with the principles of the Declaration of Helsinki. The research protocol was approved by the Local Ethics Committee of the institution mentioned in the work. Informed consent of parents or their guardians was obtained for conducting research. No conflict of interests was declared by the authors.